A Numerical model of exchange chromatography through 3‐D lattice structures. Issue 5 (22nd February 2018) - Salloum, Maher; Robinson, David B.
Abstract : Rapid progress in the development of additive manufacturing technologies is opening new opportunities to fabricate structures that control mass transport in three dimensions across a broad range of length scales. We describe a structure that can be fabricated by newly available commercial 3‐D printers. It contains an array of regular three‐dimensional flow paths that are in intimate contact with a solid phase, and thoroughly shuffle material among the paths. We implement a chemically reacting flow model to study its behavior as an exchange chromatography column, and compare it to an array of 1‐D flow paths that resemble more traditional honeycomb monoliths. A reaction front moves through the columns and then elutes. The front is sharper at all flow rates for the structure with three‐dimensional flow paths, and this structure is more robust to channel width defects than the 1‐D array. © 2018 American Institute of Chemical Engineers AIChE J, 64: 1874–1884, 2018